Perlindungan Konsumen Dalam Transaksi E-Ticketing Pending Payment dan Keterlambatan Konfirmasi E-Ticket Konser Day6 - Yulia Salsa Billa, Ainun; Budi Setianigrum, Reni (Adagium: Jurnal Ilmiah Hukum, 2025)
This study aims to examine the legal protections available to consumers in e-ticketing transactions, particularly in instances of issues such as delayed payments and confirmation of electronic tickets. The focus is on the case of the DAY6 3rd World Tour "Forever Young" concert in Jakarta, organized by the Mecimapro promoter, where numerous consumers encountered technical difficulties on the ticket sales platform, especially during payment and ticket confirmation. The research employs a normative juridical methodology, utilizing an analytical approach to Law Number 8 of 1999 on Consumer Protection (UUPK) and Law Number 1 of 2024 regarding Amendments to the ITE Law. The findings indicate that the promoters' handling of these issues did not fully align with the consumer protection principles outlined in the legislation. Indicators of inadequate implementation include a lack of accountability, insufficient information disclosure, and slow responses to consumer complaints. This research underscores the necessity for enhanced oversight, increased accountability among digital business operators, and the effective implementation of consumer complaint mechanisms.